The “Constitutive Relevance of Models” (CRoM) Test: A Tool for Transferring Constructs and Virtues between Psychological and Anthropological Theories of Ritual - Hornbeck, Ryan G. (Method & theory in the study of religion, 2022)
This paper introduces a tool designed to mitigate a longstanding challenge to developing social anthropological theories of ritual – how to generate enough comparable case studies for rigorously testing the predictive strength and generalizability of the theory under scrutiny. Our “constitutive relevance of models” (CRoM) test identifies structural continuities between anthropological and psychological theoretical models of ritual phenomena that would justify sharing some analytical tools between models. With this test, anthropologists can in certain cases draw on a psychological theory construct’s superior empirical tractability to more efficiently identify instances of ritual phenomena that are suitable for developing and testing their own anthropological models. To demonstrate, we apply a CRoM test to validate the use of a construct developed under a psychological theory of ritual, Lawson and McCauley’s “ritual form hypothesis,” to search for case studies suitable for assessing the theoretical claims that anthropologist Roy Rappaport made for “highly sacred” rituals.